Fatty tumours of the uterus. - Pounder, D J (1982)
Uterine fatty tumours (UFT) are uncommon and have received little attention in the English literature. They have aroused interest as a consequence of occasional diagnostic confusion with sarcomas and the continuing unresolved dispute as to their histogenesis. Three cases of UFT are described and the pathological features of note discussed. The viewpoint that these tumours are hamartomas/choristomas is rejected. UFT most probably represent tumour metaplasia within a leiomyoma. There is no uniform accepted nomenclature for such tumours and it is suggested that they be designated "uterine fatty tumours" and subdivided into "lipoma" and "mixed lipoma/leiomyoma" (synonym lipoleiomyoma).